Lack of correlation between micro fungi species and chemical control method of Atta treated with toxic baits - Barbosa, Marcílio Souza; Barbosa, Suzanne Nunes; Nagamoto, Nilson Satoru [UNESP]; Forti, Luiz Carlos [UNESP]; Almeida, Cícero (FapUNIFESP (SciELO), 2018)
Atta sexdens rubropilosa (leaf-cutter ants) has a symbiotic association with a fungus and has a negative interaction with other fungi due to parasitism of the fungus cultivated by ants; also, there are several other fungi with no exact known role occurring in their cultivated fungus garden. In the present study, we use the ITS region (internal transcribed spacer) to identify fungi in colonies treated with toxic baits. Experiments using two toxic baits were carried out: 0.75g of sulfluramid [0.3%] and 0.75g fipronil [0.003%]. Samples of fungi were collected and cultured in Czapek medium for seven days to allow fungal growth and subsequent identification. Total DNA was isolated from 100-150 mg of mycelium using the CTAB method and using PCR, with the universal primers (ITS4 and ITS5), to amplify the ITS region. Sequencing was performed using the Sanger method. Sequences were subjected to BLAST, allowing the identification of nine different species of the orders Agaricales, Eurotiales, Hypocreales, Pleosporales, Saccharomycetales and Tremellales showing a variation in identity of 96- 100%. Using “The Automatic Barcode Gap Discovery” analysis, nine groups were identified, corresponding to species described in NCBI. The K2P distances were used to generate a tree using Neighbour-joining, demonstrating that the species were grouped according to phylogenetic groups. We concluded that leaf-cutter ant colonies exhibited a wide variety of fungi and this study suggested that there is no correlation between the species of fungi isolated with the control method used on the ant nest.
Ausência de correlação entre espécies de microfungos e método de controle químico de Atta tratadas com iscas tóxicas
Keywords: Ants; DNA barcoding; ITS; Leaf-cutter